Dialogues between justice and vengeance in the Israel-Palestine relationship: Presentation of an initial proposal for peace - GONZALEZ JUNIOR, Francisco (Utopía y Praxis Latinoamericana, 2024)
This article aims to trace some lines of understanding of the conflict between Israel and Palestine. To do so, it employs tools from Greek mythology—in the form of the goddesses Themis and Dike—to provide minimal explanations for the onset of resentment and indignation that fuel robust processes of violence and revenge. Employing the hypothetical-deductive method, the paper advances by proposing honor as a structuring element of the social status within Arab families, and ethics as the Jewish worldview of life, supported by rituals that seek purity (kashrut). The study also innovates by presenting an initial proposal for the peace process between Israel and Palestine based on the system of total exchanges, referred to as potlatch by Marcel Mauss (2016, ebook), aiming to bridge fractures and develop an ethos of trust and overcoming pain, towards a progressive agenda of dialogue and mutual concessions.